PROTECTING THE DIGITAL REALM: A CASE STUDY OF ROMANIA’S CYBER SOVEREIGNTY - Tal, Dr. Pavel (International Journal of Legal and Social Order, 2025)
Cyber sovereignty, a nation's right to govern its cyberspace, has emerged as a critical issue in the 21st century. Indeed, cyber threats increasingly challenge national security worldwide, so cyber sovereignty has become a critical priority for nations seeking to safeguard civilian and military digital domains. Romania, a significant player in European cyber defence, has developed robust policies to safeguard its digital infrastructure and maintain sovereignty in cyberspace. This paper presents a case study of Romania's approach to cyber sovereignty, examining the strategic and legal frameworks that underpin its efforts to secure digital boundaries across civilian and military spheres. Through a detailed examination of Romania's military and national strategy and cyber-related legislative framework published in the last two decades, the research aims to illustrate how Romania addresses the demands of an evolving cybersecurity landscape and defines its cyber boundaries and sovereignty. The findings reveal a lack of well-defined cyber sovereignty in Romania. None of the 22 official strategies and policy, civilian and military, publications published between the years 2002-2021 explicitly defines the term “Cyber Sovereignty” or illustrates Romania's cyber borders; (1) Some refer to the borderless nature of cyberspace (2) others refer to Romanian cyberspace, (3) and few indicate the need to ensure cyber security and defence abroad the country and at the international level. This paper contributes to a deeper understanding of cyber sovereignty and its implementation within Romania’s national strategy and legal context. It emphasises the importance of a well-defined cyber sovereignty in Romania and worldwide.